P258 The 24-hour Lung Function Profile Of Once-daily Tiotropium And Olodaterol Fixed-dose Combination Compared With Placebo And Monotherapies In Chronic Obstructive Pulmonary Disease. (10th November 2014) - Derom, E; Westerman, J; Grönke, L; Hamilton, A; Li, C; Beeh, KM
Abstract : Introduction: Tiotropium (T), a once-daily long-acting muscarinic antagonist, is a well-established first-line maintenance treatment in chronic obstructive pulmonary disease (COPD). Olodaterol (O) is a once-daily long-acting β2 -agonist, recently approved in several EU countries. This study investigated the 24-hour bronchodilator profile of once-daily fixed-dose combinations (FDCs) of T and O delivered via the Respimat ® Soft Mist™ inhaler in patients with Global initiative for chronic Obstructive Lung Disease 2–4 COPD. Methods: This double-blind, placebo-controlled, Phase III, incomplete crossover study randomised 219 patients to receive four of the following treatments for 6 weeks (with a 3-week washout period in between): placebo, O 5 µg, T 2.5 µg, T 5 µg, T+O FDC 2.5/5 µg, T+O FDC 5/5 µg. The primary end point was forced expiratory volume in 1 second (FEV1 ) area under the curve from 0–24 h (AUC0–24 ) after 6 weeks. Secondary end points included additional spirometric parameters over 24 h and body plethysmography parameters in a sub-set of patients (2:30 and 22:30 h post-dose). Results: The 24-hour time profiles for both FDCs were similar, with clear, consistent increases in FEV1 compared to placebo and monotherapies. For FEV1 AUC0–24, both FDCs were significantly superior to placebo (T+O 5/5 µg: 0.280 L, p < 0.0001; T+O 2.5/5 µg: 0.277 L, p < 0.0001) and monotherapies (T+O 5/5 µg: 0.110–0.127 L, p < 0.0001; T+O 2.5/5 µg: 0.107–0.124 L, p < 0.0001). There were significantly greater increases in trough FEV1 with both FDCs compared to placebo (0.201–0.207 L, p < 0.0001) and monotherapies (T+O 5/5 µg: 0.079–0.107 L, p < 0.0001; T+O 2.5/5 µg: 0.073–0.101 L, p < 0.0001). In the body plethysmography sub-study, both FDC doses separated from placebo and monotherapies in functional residual capacity (p < 0.001) and residual volume (p < 0.0001). Both FDCs were well tolerated; overall incidence of adverse events ranged between 36.0% (T+O 2.5/5 µg) and 46.4% (placebo). Conclusions: Both FDC 24-hour time profiles showed clear and consistent increases in FEV1 compared to placebo and monotherapies, with a similar tolerability profile to T.